Labor policies and Philippine companies: Analysis of survey opinions - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2009)
This paper analyzes the responses from a survey of Philippine companies concerning labor market policies, such as minimum wage setting process, hiring and firing practices, training, and holidays. These policies have gained wide acceptance as a means of protecting the welfare of workers. But one of the features of the Philippine economy is the large amount of unemployment that has persisted for a long time. Specific characteristics associated with the respondent firms help to isolate important findings in their opinions about the labor policies. Matching the responses for each policy issue against certain criteria that grouped the operating enterprises, some important conclusions are derived. The firms are segregated according to whether they are recipient or non-recipient of investment incentives; export or domestic market oriented; owned by nationals or by foreigners; young or old firms, and small or large firms by size of labor employment. The policy implications for the policy are not discussed in this paper but some conclusions appear evident. Firms that complain about certain policies could be expected to be adversely affected by them.
Keywords: 330; Labor economics; employment; labor market policies; labor regulation